Genomics-Assisted Improvement of Super High-Yield Hybrid Rice Variety “Super 1000” for Resistance to Bacterial Blight and Blast Diseases - He, Zhizhou; Xin, Yeyun; Wang, Chunlian; Yang, Hanshu; Xu, Zhi; Cheng, Jihua; Li, Zhouwei; Ye, Changrong; Yin, Hexing; Xie, Zhenyu; Jiang, Nan; Huang, Jing; et al. (Frontiers in Plant Science, 2022)
The two-line rice hybrid "Super 1000" (GX24S x R900) represents a major landmark achievement of breeding for super hybrid rice in China. However, both the male parent R900 and the hybrid "Super 1000" have an obvious defect of high susceptibility to rice bacterial blight (BB) and blast. Thus, improving disease resistance and maintaining the original high-yield capacity are essential for sustainable application of "Super 1000". In this study, application of closely linked SNP markers for foreground selection of dominant resistance gene loci together with genome-wide SNP markers for background selection rapidly improved the disease resistance of R900 without disturbing its high-yield capacity. A series of improved R900 lines (iR900, in BC2Fn and BC3Fn generations) were developed to stack resistance genes (Xa23+Pi9, Xa23+Pi1+Pi2/9) by marker-assisted backcrossing and field selection for phenotypes, and further crossed with the female line GX24S to obtain improved hybrid variety Super 1000 (iS1000). The genetic backgrounds of iS1000 and “Super 1000” were profiled by using a 56 K SNP-Chip, and results showed that they shared 98.76% of similarity. Meanwhile, evaluation of field disease resistance showed that the iR900 lines and iS1000 hybrids possess significantly enhanced resistance to both BB and rice blast. Resistance spectrum assays revealed that the iR900 lines and their derived hybrids exhibited high-level resistance to 28 Xoo strains tested, and enhanced resistance to leaf blast at the seedling stage when infected with 38 M. oryzae isolates. In 2019 and 2020, the multi-location field trials across the middle and lower reaches of the Yangtze River were launched and showed that the iS1000 slightly out-yielded than the original variety. In a large-scale demonstration site (6.73 hectares, Yunnan, China), the iS1000 achieved 17.06 t/hm2 of yield in 2019. Moreover, high similarity was observed in main agronomic traits and grain quality when comparing the improved lines/hybrids to original ones (iR900 vs. R900, iS1000 vs. S1000). This work presented a typical genomics-assisted breeding strategy and practice, which involves in directional introgression and rapid stack of multiple disease resistance genes, endowing the super high-yield hybrid rice variety with holistic disease resistance but without yield penalty.